Deformed microbial mat structures in a semiarid temperate coastal setting - Cuadrado, Diana Graciela (2015)
This study focuses on sedimentary structures formed by microbial consortia, in a particular coastal setting, an ancient tidal channel, separated from the ocean by a sandy spit and connected by a blind tidal channel at the opposite end. Most studies in modern and ancient environments consider water movement as the triggering mechanism acting in the formation and deformation of sedimentary structures. As such, the paper documents the presence of several microbial structures such as shrinkage cracks, flip-over mats, microbial chips, and multidirectional ripples which are related to tidal processes, while bulges and gas domes structures are formed after occasional inundation events. However, the more conspicuous structures covering a great area at the study site are folds and roll-ups, the product of deformation of microbially induced structures by the action of sporadic spring-tidal currents due to strong winds. Therefore, the objective of this research is to document modern sedimentary structures in a coastal area and to provide a mechanistic explanation for their formation, based on the interplaying effects of the moisture variation and high shear stress. Also, several microbial sedimentary structures are distinguished throughout vertical sediment cores, such as microbial chips, detached mat, sponge fabrics, tears, and concentric structures, which are identified in a sedimentary profile. Through the recognition and interpretation of modern sedimentary deformation structures, this study contributes empirical tools for the reconstruction of analogous paleoenvironments in fossil studies.